Transfusion support by a UK Role 1 medical team: a 2-year experience from Afghanistan. Issue 6 (23rd September 2015) - Aye Maung, Niall; Doughty, H; MacDonald, S; Parker, P
Abstract : Introduction: This paper describes the clinical governance, training, equipment and infrastructure developed to enable a UK Role 1 medical team to deliver forward transfusion in Southern Afghanistan. The aim was to explore the utility and feasibility of forward blood transfusion by a Role 1 medical team in an austere military environment. Methods: An audit of prospectively collected transfusion regulatory and cold chain data using standard-issue equipment and governance systems. TempIT tags were read before and after each mission to record blood storage temperature. Two years' data were analysed to review the use of blood products, cold chain compliance and equipment issues. Results: Over 24 months, blood products were carried on over 1000 mission hours. Two clinical cases required transfusion and were successfully resuscitated. The team was able to correctly transport, store and deploy red cells and plasma on missions using standard Ministry of Defence (MOD) issue equipment. There were seven cold chain failures, all of which were addressed locally. Current cold chain and diagnostic equipment would require further optimisation for use at Role 1. Conclusions: An isolated Role 1 medical team can safely deliver blood transfusion on vehicle, helicopter or foot patrols. The transport and storage of blood created a large logistical burden for a relatively small clinical output. However, with further developments, this capability may have utility in contingency operations especially for isolated teams.